Utilization of Technological Innovation in the Transfer of Receivables through Cessie for the Resolution of Non-Performing Loans - Selviana, Devi; Tan, David; Syarief, Elza (IHSA Institute, 2025)
This study explores the potential use of technological innovation in the transfer of receivables through cessie as a solution to the rising issue of non-performing loans in Indonesia’s financial sector. The research employs a normative juridical method, without quantitative data, relying entirely on legal literature and doctrinal analysis. Using statutory and case approaches, it analyzes the legal framework and case examples relevant to digital receivables transfer. The study specifically aims to examine (1) how fintech and blockchain contribute to the efficiency and transparency of cessie transactions, (2) how Indonesian regulations adapt to digital cessie mechanisms, and (3) the legal obstacles in implementing these technologies. The findings reveal that fintech enables faster, more accessible receivables trading, while blockchain provides secure, verifiable transaction records. However, implementation faces significant regulatory challenges, such as the absence of explicit legal recognition for electronic contracts and a lack of standardized digital procedures for debtor notification, as required by Article 613 of the Indonesian Civil Code. The study recommends regulatory reforms to legally recognize smart contracts and formalize digital notification procedures. Improving digital infrastructure and ensuring legal certainty will be essential to support the broader integration of digital cessie practices into Indonesia’s financial legal system